2021
DOI: 10.1177/02692163211030831
|View full text |Cite
|
Sign up to set email alerts
|

Trends in quality of care and dying perceived by family caregivers of nursing home residents with dementia 2005–2019

Abstract: Background: Dementia palliative care is increasingly subject of research and practice improvement initiatives. Aim: To assess any changes over time in the evaluation of quality of care and quality of dying with dementia by family caregivers. Design: Combined analysis of eight studies with bereaved family caregivers’ evaluations 2005–2019. Setting/participants: Family caregivers of nursing home residents with dementia in the Netherlands ( n = 1189) completed the End-of-Life in Dementia Satisfaction With Care (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In our study, the offspring's support for the medical and care costs of patients support the abovementioned opinion. In conclusion, palliative care and quality of life are increasingly emphasized in Western countries [33,34], while in China, the survival period is still the paramount consideration, followed by quality of life. A positive treatment attitude explains the outcome in this study, i.e., longer survival of patients with advanced dementia in China compared to other countries.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the offspring's support for the medical and care costs of patients support the abovementioned opinion. In conclusion, palliative care and quality of life are increasingly emphasized in Western countries [33,34], while in China, the survival period is still the paramount consideration, followed by quality of life. A positive treatment attitude explains the outcome in this study, i.e., longer survival of patients with advanced dementia in China compared to other countries.…”
Section: Discussionmentioning
confidence: 99%
“…6 The quality of end-of-life care and death experience is shaped by the care needs, preferences and experiences of both the person with dementia, and their carer and family. 47 The needs of family carers and the person with dementia are often interdependent (but not always congruent). 5,48 For example, interviews with residential aged care staff and review of case notes for people enrolled in the MMPC model of care revealed several instances in which the person with dementia had an advance care directive but their family member was reluctant for it to be followed.…”
Section: Integration Of Carementioning
confidence: 99%
“…For its evaluation, we planned qualitative interviews, and in the nursing homes affiliated with the organization also a pre-post-test survey for bereaved family [10]. We prepared for a main, controlled study with adequate power involving another large care organization in case the pilot was successful.…”
Section: Introductionmentioning
confidence: 99%